A hydrogenation catalyst, its preparation method and use
Patent Information
- Application Number
- CN202311402068.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-26
AI Technical Summary
但大部分碳三催化剂对原料中的碳四馏分的含量有一定要求,同时大部分碳四催化剂也对原料中的MAPD转化率较低
[0056]本发明通过在载体制备过程中添加适量的等电点调控剂,再根据加入的等电点调控剂有针对性地对成型的氧化铝载体进行表面处理,例如,结合酸化或碱化、晶化、辐照中至少两种处理方法,从而实现氧化铝载体表面羟基基团密度的显著提升,促进金属活性组分负载在载体上,提高得到催化剂对不饱和烃的转化率。本发明提供的加氢催化剂可将轻质化原料裂解装置产生的碳三碳四馏分中的不饱和烃全加氢至饱和,可以作为裂解或其他原料使用。
Smart Images

Figure BDA0004516937630000121 
Figure BDA0004516937630000131 
Figure BDA0004516937630000132
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to a hydrogenation catalyst, its preparation method, and its application. Background Technology
[0002] In recent years, cracking feedstocks have shown a diversified development trend, with the use of lighter feedstocks receiving particular attention. Currently, the main feedstocks used in ethylene plants both domestically and internationally are naphtha, ethane, propane, butane, diesel, and coal. Compared to traditional naphtha cracking, light hydrocarbon cracking units offer advantages such as shorter process flow, smaller footprint, lower investment, and higher yields. Besides the main product, ethylene, cracking units using lighter feedstocks produce byproducts such as hydrogen, methane, C3, C4 hydrocarbons, benzene, and toluene. The unsaturated C3 and C4 hydrocarbons are present in relatively small amounts, primarily including propylene, propyne (MA), propadiene (PD), butadiene, and butene. Separating these components and then hydrogenating them individually is costly; therefore, they are typically fully hydrogenated before being transported to the cracking furnace as cracking feedstock.
[0003] Chinese patent CN105727990A discloses a C3 selective hydrogenation catalyst and its preparation method. It uses Al2O3 modified with an organic solution of a hydroxyl-containing bipyridine derivative as a support and a mixed cationic solution of palladium and copper as a precursor of the active component. By modifying the support, the surface tension and solvation effect of the impregnation solution are overcome, resulting in better dispersion of palladium-copper, which is more conducive to the formation of palladium-copper alloy and has better selectivity and anti-coking properties.
[0004] Chinese patent CN114100615A discloses a C4 selective hydrogenation catalyst and its preparation method, which uses a modified attapulgite-montmorillonite composite material as a support and non-precious metal nickel as the active component. The nickel source can be nickel salt or basic nickel carbonate extracted from spent nickel-hydrogen batteries. Acid-base synergistic catalysis is achieved through the stepped pores formed within the crystals of the composite support, giving the catalyst good activity and selectivity.
[0005] Existing technologies primarily target the separate hydrogenation of C3 or C4 fractions, or the layering of C3 and C4 hydrogenation catalysts in the hydrogenation reactor for the mixed stream. However, most C3 catalysts have certain requirements regarding the C4 fraction content in the feedstock, and most C4 catalysts also exhibit low MAPD conversion rates in the feedstock. Therefore, there is a need to develop a full hydrogenation catalyst suitable for mixed C3 and C4 fractions generated by light feedstock cracking units. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention proposes a hydrogenation catalyst that can be used for the full hydrogenation of C3 and C4 mixed fractions produced by the cracking of lighter feedstocks, and can be used as cracking or other feedstocks after hydrogenating olefins and dienes to saturation.
[0007] One of the objectives of this invention is to provide a hydrogenation catalyst, comprising: a support, and a main active component and a co-active component supported on the support, wherein the support is a modified alumina support rich in hydroxyl groups on its surface.
[0008] According to the present invention, in the hydrogenation catalyst:
[0009] The carrier is a modified alumina carrier obtained by adding an isoelectric point modifier to an alumina-containing component and then performing surface treatment.
[0010] The density of hydroxyl groups on the surface of the carrier is 6–18 mmol / m³. 2 The preferred value is 6.5–15 mmol / m². 2 ;
[0011] The average pore size of the carrier is 50–200 nm, and the most probable pore size is 100–350 nm; preferably, the average pore size of the carrier is 70–180 nm, and the most probable pore size is 110–300 nm.
[0012] The specific surface area of the carrier is 5–280 m². 2 / g, preferably 15-250m 2 / g;
[0013] The bulk density of the carrier is 0.35–1.2 g / mL, preferably 0.45–1 g / mL.
[0014] According to the present invention, in the hydrogenation catalyst:
[0015] The main active component is Pd;
[0016] The auxiliary active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, and alkaline earth metals, preferably at least one of Ag, Ga, Zn, Cu, Pb, Ce, and In;
[0017] The carrier contains aluminum oxide and other oxides, wherein the other oxides are selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, titanium oxide, ferrous oxide, cerium oxide, nickel oxide, iron oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.
[0018] According to the present invention, in the hydrogenation catalyst:
[0019] Based on the total weight of the carrier (100%), the content of the main active component is 0.05-0.5%, and the content of the auxiliary active component is 0.01-10%; preferably, based on the total weight of the carrier (100%), the content of the main active component is 0.1-0.4%, and the content of the auxiliary active component is 0.01-5%.
[0020] Based on the total weight of the carrier (100%), the alumina content is 60-99.9%, preferably 65-98%.
[0021] A second objective of this invention is to provide a method for preparing the aforementioned hydrogenation catalyst. This method allows for the loading of the main active component and the auxiliary metal component onto a support using any existing method for preparing supported catalysts. For example, the active component precursor can be loaded onto the support using a spraying method and / or an impregnation method. Specifically, the method for preparing the hydrogenation catalyst includes: impregnating the support with a metal compound solution containing the main active component precursor compound and the auxiliary metal component precursor compound, followed by drying and calcination to obtain the hydrogenation catalyst.
[0022] According to the present invention, in the method for preparing the hydrogenation catalyst:
[0023] The main active component precursor compound is selected from palladium nitrate, palladium chloride, palladium oxide, palladium hydroxide, and sodium tetrachloropalladate, preferably from at least one of palladium nitrate and palladium chloride;
[0024] The precursor compound for the auxiliary active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, chlorides, nitrates, acetates, sulfates of alkaline earth metals, and organometallic compounds, preferably from at least one of chlorides and nitrates of Ag, Ga, Zn, Cu, Pb, Ce, and In;
[0025] In the metal compound solution, the concentration of the main active component precursor compound is 5-100 mg / mL, wherein the main active component precursor compound is calculated based on the metal it contains;
[0026] The solvent in the metal compound solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid, and alcohols, preferably water;
[0027] The drying process can employ commonly used drying equipment and conditions in the prior art. For example, the drying conditions are: a drying temperature of 40–180°C and a drying time of 2–24 hours; preferably, the drying temperature is 50–170°C and the drying time is 4–20 hours.
[0028] The roasting can be carried out using roasting equipment and roasting conditions commonly used in the prior art. For example, the roasting conditions are: roasting temperature of 200-600℃ and roasting time of 2-10h; preferably, roasting temperature of 300-550℃ and roasting time of 4-10h.
[0029] According to the present invention, the preparation of the carrier includes the following steps:
[0030] (1) Mix the components including aluminum source, forming agent, pore expander, isoelectric point regulator, and crosslinking agent solution to obtain a mixture;
[0031] (2) The mixture obtained in step (1) is kneaded, extruded, granulated, dried, and calcined to obtain a modified alumina precursor;
[0032] (3) The modified alumina precursor obtained in step (2) is subjected to surface treatment to obtain the carrier.
[0033] According to the present invention, in the method for preparing the carrier:
[0034] The aluminum source is selected from at least one of boehmite, pseudoboehmite, alumina, and aluminum hydroxide;
[0035] The molding agent is selected from at least one of starch, methylcellulose, carboxymethylcellulose, ethylcellulose, and hydroxyethylcellulose;
[0036] The pore-expanding agent is selected from at least one of guar gum powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol;
[0037] The isoelectric point modifier is selected from at least one of oxides with an isoelectric point less than 6.5 or greater than 8.5. Preferably, the isoelectric point modifier with an isoelectric point less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; and / or, the isoelectric point modifier with an isoelectric point greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.
[0038] The crosslinking agent in the crosslinking agent solution is selected from at least one of inorganic acids and organic acids, preferably from at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid, and salicylic acid;
[0039] The solvent in the crosslinking agent solution is selected from at least one of water and organic solvents, preferably from at least one of water, methanol, and ethanol.
[0040] According to the present invention, in the method for preparing the carrier:
[0041] Based on the total weight of the aluminum source, forming agent, pore expander, and isoelectric point control agent as 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expander is 0.1-10%, the amount of the isoelectric point control agent is 0.01-20%, and the remainder is the aluminum source; preferably, based on the total weight of the aluminum source, forming agent, pore expander, and isoelectric point control agent as 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expander is 0.5-8%, the amount of the isoelectric point control agent is 0.05-15%, and the remainder is the aluminum source;
[0042] Based on the amount of aluminum source used being 100g, the amount of crosslinking agent solution used is 50-180mL, preferably 70-160mL;
[0043] The molar concentration of the crosslinking agent solution is 0.001–10 mol / L, preferably 0.01–6 mol / L.
[0044] According to the present invention, in the method for preparing the carrier:
[0045] The carrier can be formed using any existing forming technology in the art, such as at least one of fluidized granulation, agglomeration granulation, extrusion granulation, compression granulation or spray granulation.
[0046] The calcination conditions in step (2) are: calcination at 350-1200℃ for 1-10 hours, preferably calcination at 500-1150℃ for 2-8 hours;
[0047] In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. Preferably, when the isoelectric point regulator is an oxide with an isoelectric point less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.2 to 1 higher; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5, acidification is not used, and alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator, preferably 0.3 to 3.5 higher;
[0048] The modified alumina obtained after surface treatment in step (3) still needs to be dried. Common drying conditions can be used to ensure that the modified alumina is dry.
[0049] According to the present invention, in the method for preparing the carrier:
[0050] The acidification conditions are as follows: the acidifier in the acidifying agent solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, ascorbic acid, hydrogen peroxide, and potassium permanganate; the concentration of the acidifier in the acidifying agent solution is 0.001–5 mol / L; the acidification temperature is 30–80°C; and the acidification time is 0.5–8 h. Preferably, the concentration of the acidifier in the acidifying agent solution is 0.01–4 mol / L; the acidification temperature is 35–75°C; and the acidification time is 1–6 h.
[0051] The alkalization conditions are as follows: the alkalizing agent in the alkalizing agent solution is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate; the concentration of the alkalizing agent in the alkalizing agent solution is 0.005–5 mol / L; the alkalization temperature is 30–80℃; and the alkalization time is 0.5–8 h. Preferably, the concentration of the alkalizing agent in the alkalizing agent solution is 0.01–4 mol / L; the alkalization temperature is 35–75℃; and the alkalization time is 1–6 h.
[0052] The crystallization conditions are as follows: the solvent used for crystallization is at least one of water, methanol, and ethanol; the crystallization temperature is 120–250°C; and the crystallization time is 0.5–18 h. Preferably, the solvent used for crystallization is at least one of water and ethanol; the crystallization temperature is 150–200°C; and the crystallization time is 1–6 h.
[0053] The irradiation conditions are as follows: the radiation source is gamma rays, the irradiation dose rate is 0.01–50 kGy / min, and the irradiation time is 0.2–12 h; preferably, the radiation source is gamma rays, the irradiation dose rate is 0.1–25 kGy / min, and the irradiation time is 0.2–6 h.
[0054] In this invention, the alumina carrier and its preparation can be referred to patent ZL202311114679.2, and the relevant content disclosed in the aforementioned document is incorporated herein by reference.
[0055] A third objective of this invention is to provide the application of the above-mentioned hydrogenation catalyst, or the hydrogenation catalyst obtained by the above-mentioned preparation method, in the full hydrogenation reaction of a C3-C4 mixed fraction. The "full hydrogenation of a C3-C4 mixed fraction" refers to hydrogenating unsaturated hydrocarbons in a C3-C4 mixture produced by a cracking unit until saturated, and then feeding it to the cracking furnace as a feedstock or for use as other feedstocks.
[0056] This invention significantly increases the density of hydroxyl groups on the alumina support surface by adding an appropriate amount of isoelectric point modifier during the support preparation process, and then selectively treating the formed alumina support according to the added isoelectric point modifier. For example, it combines at least two of the following treatment methods: acidification or alkalization, crystallization, and irradiation. This promotes the loading of metal active components onto the support and improves the conversion rate of unsaturated hydrocarbons in the resulting catalyst. The hydrogenation catalyst provided by this invention can fully hydrogenate unsaturated hydrocarbons in the C3 and C4 fractions produced by a light feedstock cracking unit to saturation, and can be used as a cracking or other feedstock. Detailed Implementation
[0057] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0058] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0059] Example 1
[0060] 1. Preparation of the molding carrier
[0061] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 2 5g of polyethylene glycol, 6g of guar gum powder, and 4g of silica (isoelectric point 2.5) were mixed evenly in a kneader. 2g of concentrated sulfuric acid and 3g of citric acid were added to 100mL of deionized water to prepare a mixed solution. The prepared solution was added to the kneader, and after kneading, it was rolled into spherical particles with a diameter of 5mm using a ball-forming machine. These particles were dried at 60℃ for 6h, calcined at 1150℃ for 6h, acidified with 100mL of hydrochloric acid solution (pH 3.0) at 40℃ for 1h, and finally crystallized in 20wt% ethanol aqueous solution at 150℃ for 2h, dried at 120℃ for 6h, and irradiated with 0.8kGy / min γ-rays for 4h to obtain alumina support S1.
[0062] 2. Preparation of selective hydrogenation catalysts
[0063] 0.16 g of silver nitrate and 0.68 g of zinc nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL). The solution was diluted with deionized water to 45.0 mL and sprayed onto 100 g of alumina support S1. The sprayed sample was dried in an oven at 110 °C for 10 h and then calcined at 500 °C for 8 h to obtain catalyst C1, with a Pd loading of 0.25 wt%, an Ag loading of 0.10 wt%, and a zinc loading of 0.15 wt%.
[0064] Example 2
[0065] 1. Preparation of the molding carrier
[0066] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 2 2g of hydroxymethyl cellulose, 3g of starch, and 5g of tungsten trioxide (isoelectric point 0.4) were mixed evenly in a kneader. 1.2g of concentrated sulfuric acid and 0.8g of concentrated nitric acid were weighed and added to 100mL of deionized water to prepare a mixed solution. The prepared solution was added to the kneader, and after kneading, it was rolled into spherical particles with a diameter of 5mm using a ball-forming machine. The particles were dried at 60℃ for 6h, calcined at 1000℃ for 6h, and then crystallized in air at 170℃ for 5h. The particles were then acidified with 100mL of sulfuric acid solution (pH 1) at 50℃ for 1h, and finally dried at 120℃ for 6h to obtain alumina support S2.
[0067] 2. Preparation of selective hydrogenation catalysts
[0068] 0.76 g of copper nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL), diluted with deionized water to 45.0 mL, and sprayed onto 100 g of alumina support S2. The sprayed sample was dried in an oven at 110 °C for 10 h and then calcined at 500 °C for 8 h to obtain catalyst C2, with a Pd loading of 0.25 wt% and a Cu loading of 0.2 wt%.
[0069] Example 3
[0070] 1. Preparation of the molding carrier
[0071] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 25g of guar gum powder, 4g of starch, and 7g of zirconium oxide (isoelectric point 6.0) were mixed evenly in a kneader. 1.5g of nitric acid and 2.5g of citric acid were added to 100mL of deionized water to prepare a mixed solution. The prepared solution was added to the kneader, and after kneading, it was rolled into spherical particles with a diameter of 5mm using a ball-forming machine. These particles were dried at 60℃ for 6h, calcined at 950℃ for 6h, irradiated with γ-rays at 4kGy / min for 3h, and finally acidified in 100mL of acetic acid solution (pH 6.5) at 50℃ for 4h, and then dried at 120℃ for 6h to obtain alumina support S3.
[0072] 2. Preparation of selective hydrogenation catalysts
[0073] 0.32 g of silver nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL), diluted with deionized water to 45.0 mL, and sprayed onto 100 g of alumina support S3. The sprayed sample was dried in an oven at 110 °C for 10 h and then calcined at 500 °C for 8 h to obtain catalyst C3, with a Pd loading of 0.25 wt% and an Ag loading of 0.20 wt%.
[0074] Example 4
[0075] 1. Preparation of the molding carrier
[0076] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 2 Alumina carrier S4 was prepared by mixing 3g methylcellulose, 4g polypropylene glycol, 6g copper oxide (isoelectric point 9.3), and 5g lanthanum oxide (isoelectric point 10.0) in a kneader. 3g acetic acid and 2g hydrochloric acid were added to 100mL of deionized water to prepare a mixed solution. The prepared solution was added to the kneader, kneaded, and then rolled into spherical particles with a diameter of 5mm using a ball-forming machine. The particles were dried at 60℃ for 6h, calcined at 1050℃ for 6h, irradiated with γ-rays at 2kGy / min for 5h, crystallized in 200mL of water at 200℃ for 3h, and finally alkalized in 100mL of sodium carbonate solution (pH 10.3) at 60℃ for 2h, and then dried at 120℃ for 6h.
[0077] 2. Preparation of selective hydrogenation catalysts
[0078] 0.16 g of silver nitrate and 0.37 g of gallium nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL). The solution was diluted with deionized water to 45.0 mL and sprayed onto 100 g of alumina support S4. The sprayed sample was dried in an oven at 110 °C for 10 h and then calcined at 500 °C for 8 h to obtain catalyst C4, with a Pd loading of 0.25 wt%, an Ag loading of 0.10 wt%, and a Ga loading of 0.10 wt%.
[0079] Example 5
[0080] 1. Preparation of the molding carrier
[0081] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 2 4g of guar gum powder, 5g of polyacrylamide, and 5g of zinc oxide (isoelectric point 9.0) were mixed evenly in a kneader. 5g of oxalic acid was added to 100mL of deionized water to prepare a mixed solution. The prepared solution was added to the kneader, and after kneading, it was rolled into spherical particles with a diameter of 5mm using a ball-forming machine. These particles were dried at 60℃ for 6h, calcined at 700℃ for 6h, irradiated with γ-rays at 1kGy / min for 6h, crystallized in nitrogen at 160℃ for 5h, and finally dried at 120℃ for 6h to obtain alumina support S5.
[0082] 2. Preparation of selective hydrogenation catalysts
[0083] 0.24 g of lead nitrate was weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL), diluted with deionized water to 45.0 mL, and sprayed onto 100 g of alumina support S5. The sprayed sample was placed in an oven and dried at 110 °C for 10 h, then calcined at 500 °C for 8 h to obtain catalyst C5 with a Pd loading of 0.25 wt% and a Pb loading of 0.15 wt%.
[0084] Example 6
[0085] 1. Preparation of the molding carrier
[0086] Weigh out 100g of pseudoboehmite (specific surface area 274.9m²). 25g starch, 4g polyethylene glycol, and 5g indium oxide (isoelectric point 8.8) were mixed evenly in a kneader. 3g concentrated hydrochloric acid was added to 100mL deionized water to prepare a mixed solution. The prepared solution was added to the kneader, and after kneading, it was rolled into spherical particles with a diameter of 5mm using a ball-forming machine. These particles were dried at 60℃ for 6h, calcined at 900℃ for 6h, alkalized in 100mL potassium bicarbonate solution (pH 9.5) at 60℃ for 5h, and finally irradiated with 5kGy / min γ-rays for 3h to obtain alumina support S6.
[0087] 2. Preparation of selective hydrogenation catalysts
[0088] 0.40 g of cerium nitrate and 0.39 g of indium nitrate were weighed and added to 25 mL of palladium nitrate solution (Pd content 10 mg / mL). The solution was diluted with deionized water to 45.0 mL and sprayed onto 100 g of alumina support S6. The sprayed sample was dried in an oven at 110 °C for 10 h and then calcined at 500 °C for 8 h to obtain catalyst C6, with a Pd loading of 0.25 wt%, a Ce loading of 0.10 wt%, and an In loading of 0.15 wt%.
[0089] Comparative Example 1
[0090] The support was prepared according to the method of Example 1, without the addition of an isoelectric point modifier, and without crystallization, acidification, or irradiation treatment after high-temperature calcination, to obtain support S7. The catalyst was prepared using the same method as in Example 1 to obtain catalyst D1.
[0091] Comparative Example 2
[0092] The support was prepared according to the method of Example 1, and after high-temperature calcination, it was not subjected to crystallization, acidification, or irradiation treatment to obtain support S8. The catalyst was prepared according to Example 1 to obtain catalyst D2.
[0093] Comparative Example 3
[0094] The support was prepared according to the method of Example 4, and after high-temperature calcination, it was not subjected to crystallization, alkalization, or irradiation treatment to obtain support S9. The catalyst was prepared according to Example 4 to obtain catalyst D3.
[0095] Comparative Example 4
[0096] The support was prepared according to the method of Example 1, and after high-temperature calcination, no crystallization or irradiation treatment was performed to obtain support S10. The catalyst was prepared according to Example 1 to obtain catalyst D4.
[0097] Comparative Example 5
[0098] The support was prepared according to the method of Example 1, and after high-temperature calcination, no acidification or irradiation treatment was performed to obtain support S11. The catalyst was prepared according to Example 1 to obtain catalyst D5.
[0099] Comparative Example 6
[0100] The support was prepared according to the method of Example 4, and after high-temperature calcination, no crystallization or alkalization treatment was performed to obtain support S12. The catalyst was prepared according to Example 4 to obtain catalyst D6.
[0101] The testing instruments and conditions used in the examples and comparative examples are as follows:
[0102] Specific surface area was measured using the nitrogen physical adsorption BET method;
[0103] The bulk density was calculated by measuring the mass of 100 mL of alumina carrier, and the average value was taken after measuring each sample three times.
[0104] The pore volume and most probable pore size were determined by mercury intrusion porosimetry.
[0105] Method for measuring surface hydroxyl density: Weigh 0.1 g of the support and place it in a quartz tube. Pre-treat it under argon at 450 °C for 0.5 h. Then, start the in-situ hydrogen-deuterium exchange experiment. Record the changes in hydrogen and deuterium signals using a mass spectrometer. The density of hydroxyl groups on the support surface is then calculated using specific surface area and mass normalization.
[0106] The physical property test results of the alumina supports prepared in the examples and comparative examples are shown in Table 1.
[0107] Table 1. Test results of alumina carriers in the examples and comparative examples.
[0108]
[0109] As shown in Table 1, the alumina support prepared by the method described in this invention exhibits significantly higher content and density of hydroxyl groups on its surface. Furthermore, the density of hydroxyl groups on the alumina support surface can be precisely controlled by adjusting the type and ratio of raw materials, isoelectric point species, and corresponding surface treatment methods.
[0110] Test case
[0111] 20 mL of the catalyst from the above examples and comparative examples was added to an adiabatic fixed-bed reactor. A C3-C4 mixed feedstock was fed from top to bottom into a selective hydrogenation reactor. The reactor inlet temperature was 45°C, the pressure was 3.0 MPa, and the liquid hourly space velocity (LHSV) calculated based on the feed rate was 60 h⁻¹. -1 The raw materials were evaluated according to the following conditions. The composition of the raw materials is shown in Table 2, and the evaluation results are shown in Table 3.
[0112] Among them, gas chromatography was used to detect the component content of the raw materials and the materials after hydrogenation with various catalysts.
[0113] Unsaturated hydrocarbon conversion rate = (molar content of unsaturated hydrocarbons in the feedstock - molar content of unsaturated hydrocarbons in the product) / molar content of unsaturated hydrocarbons in the feedstock * 100%
[0114] Table 2. Raw material composition
[0115]
[0116] (Where, MAPD represents the total amount of propyne and propadiene.)
[0117] Table 3 Catalyst Evaluation Results
[0118]
[0119] The component contents in the hydrogenated products in Table 3 are weight percentages calculated after deducting the hydrogen content and normalizing. Results from the application of the above catalyst to the full hydrogenation of C3 and C4 mixed fractions show that the catalyst of this invention can completely react the dienes in the mixed fractions, and achieve a higher conversion rate of unsaturated hydrocarbons.
Claims
1. A hydrogenation catalyst, comprising: The carrier, and the main active component and the co-active component loaded on the carrier, wherein the carrier is a modified alumina carrier with a surface rich in hydroxyl groups; The carrier is a modified alumina carrier obtained by adding an isoelectric point modifier to an alumina-containing component and then performing surface treatment. The isoelectric point modifier is selected from at least one oxide with an isoelectric point less than 6.5 or greater than 8.
5. The surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation. When the isoelectric point modifier is an oxide with an isoelectric point less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.1-2 higher than the isoelectric point value of the isoelectric point modifier. For oxides with an isoelectric point greater than 8.5, when acidification is not used and alkalization is used, the pH of the alkalization treatment needs to be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator; the isoelectric point regulator with an isoelectric point less than 6.5 is selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, and titanium oxide; the isoelectric point regulator with an isoelectric point greater than 8.5 is selected from at least one of cerium oxide, nickel oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.
2. The hydrogenation catalyst according to claim 1, characterized in that, The carrier has an average pore size of 50-200 nm and a most probable pore size of 100-350 nm; and / or, The specific surface area of the carrier is 5~280m². 2 / g; and / or, The bulk density of the carrier is 0.35~1.2 g / mL.
3. The hydrogenation catalyst according to claim 2, characterized in that, The carrier has an average pore size of 70-180 nm and a most probable pore size of 110-300 nm; and / or, The specific surface area of the carrier is 15~250m². 2 / g; and / or, The bulk density of the carrier is 0.45~1g / mL.
4. The hydrogenation catalyst according to claim 1, characterized in that, The main active component is Pd; and / or, The co-active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, and alkaline earth metals; and / or, The carrier contains aluminum oxide and other oxides, wherein the other oxides are selected from at least one of tungsten trioxide, vanadium pentoxide, antimony pentoxide, silicon oxide, zirconium oxide, manganese oxide, tin oxide, titanium oxide, ferrous oxide, cerium oxide, nickel oxide, iron oxide, copper oxide, zinc oxide, lanthanum oxide, gallium oxide, and indium oxide.
5. The hydrogenation catalyst according to claim 4, characterized in that, The active ingredient is selected from at least one of Ag, Ga, Zn, Cu, Pb, Ce, and In.
6. The hydrogenation catalyst according to claim 1, characterized in that, Based on the total weight of the carrier (100%), the content of the main active component is 0.05-0.5%, and the content of the auxiliary active component is 0.01-10%; and / or, Based on the total weight of the carrier being 100%, the alumina content is 60-99.9%.
7. The hydrogenation catalyst according to claim 1, characterized in that, Based on the total weight of the carrier (100%), the content of the main active component is 0.1-0.4%, and the content of the auxiliary active component is 0.01-5%; and / or, Based on the total weight of the carrier being 100%, the alumina content is 65-98%.
8. A method for preparing the hydrogenation catalyst according to any one of claims 1 to 7, comprising: The support is impregnated with a metal compound solution containing the main active component precursor compound and the auxiliary metal component precursor compound, and then dried and calcined to obtain the hydrogenation catalyst.
9. The preparation method according to claim 8, characterized in that, The main active component precursor compound is selected from one of palladium nitrate, palladium chloride, palladium oxide, palladium hydroxide, and sodium tetrachloropalladate; and / or, The precursor compound for the co-active component is selected from at least one of Ag, Ga, Bi, Ce, Pb, Cu, Au, Zn, Ga, In, Cu, As, rare earth metals, alkali metals, chlorides, nitrates, acetates, sulfates of alkaline earth metals, and organometallic compounds; and / or, In the metal compound solution, the concentration of the main active component precursor compound is 5-100 mg / mL, wherein the main active component precursor compound is calculated based on the metal it contains; and / or, The solvent in the metal compound solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid, and alcohols; and / or, The drying conditions are: a drying temperature of 40~180℃, and a drying time of 2~24h; and / or, The calcination conditions are: calcination temperature of 200~600℃ and calcination time of 2~10h.
10. The preparation method according to claim 9, characterized in that, The main active component precursor compound is selected from at least one of palladium nitrate and palladium chloride; and / or, The precursor compound for the co-active component is selected from at least one of the chlorides and nitrates of Ag, Ga, Zn, Cu, Pb, Ce, and In; and / or, The solvent in the metal compound solution is water; and / or, The drying conditions are: a drying temperature of 50~170℃, and a drying time of 4~20h; and / or, The calcination conditions are: calcination temperature of 300~550℃ and calcination time of 4~10h.
11. The preparation method according to claim 8, characterized in that, The preparation of the carrier includes the following steps: (1) Mix the components including aluminum source, forming agent, pore expander, isoelectric point regulator, and crosslinking agent solution to obtain a mixture; (2) The mixture obtained in step (1) is kneaded, extruded, granulated, dried, and calcined to obtain the modified alumina precursor; (3) The modified alumina precursor obtained in step (2) is subjected to surface treatment to obtain the carrier.
12. The preparation method according to claim 11, characterized in that, The aluminum source is selected from at least one of boehmite, pseudoboehmite, alumina, and aluminum hydroxide; and / or, The molding agent is selected from at least one of starch, methylcellulose, carboxymethylcellulose, ethylcellulose, and hydroxyethylcellulose; and / or, The pore-expanding agent is selected from at least one of guar gum powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol; and / or, The isoelectric point modifier is selected from at least one of oxides with an isoelectric point less than 6.5 or greater than 8.5; and / or, The crosslinking agent in the crosslinking agent solution is selected from at least one of inorganic acids and organic acids; and / or, The solvent in the crosslinking agent solution is selected from at least one of water and organic solvents.
13. The preparation method according to claim 12, characterized in that, The crosslinking agent in the crosslinking agent solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, formic acid, acetic acid, citric acid, oxalic acid, ascorbic acid, and salicylic acid; and / or, The solvent in the crosslinking agent solution is selected from at least one of water, methanol, and ethanol.
14. The preparation method according to claim 11, characterized in that, Based on the total weight of the aluminum source, forming agent, pore expander, and isoelectric point control agent being 100%, the amount of the forming agent is 0.1-10%, the amount of the pore expander is 0.1-10%, and the amount of the isoelectric point control agent is 0.01-20%; and / or, Based on an aluminum source dosage of 100g, the amount of the crosslinking agent solution is 50-180mL; and / or, The molar concentration of the crosslinking agent solution is 0.001~10 mol / L.
15. The preparation method according to claim 14, characterized in that, Based on the total weight of the aluminum source, forming agent, pore expander, and isoelectric point control agent being 100%, the amount of the forming agent is 0.5-8%, the amount of the pore expander is 0.5-8%, and the amount of the isoelectric point control agent is 0.05-15%; and / or, Based on an aluminum source dosage of 100g, the amount of the crosslinking agent solution is 70-160mL; and / or, The molar concentration of the crosslinking agent solution is 0.01~6 mol / L.
16. The preparation method according to claim 11, characterized in that, The calcination conditions in step (2) are: calcination at 350~1200℃ for 1~10 hours; and / or, In step (3), the surface treatment is selected from at least two of acidification or alkalization, crystallization, and irradiation; and / or, The modified alumina obtained after surface treatment in step (3) still needs to be dried.
17. The preparation method according to claim 16, characterized in that, The calcination conditions in step (2) are: calcination at 500~1150℃ for 2~8 hours; and / or, When the isoelectric point regulator is an oxide with an isoelectric point less than 6.5 and acidification is used, the pH of the acidification treatment must be 0.1 to 2 higher than the isoelectric point value of the isoelectric point regulator; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and alkalization is used instead of acidification, the pH of the alkalization treatment must be 0.1 to 4 higher than the isoelectric point value of the isoelectric point regulator.
18. The preparation method according to claim 17, characterized in that, When the isoelectric point regulator is an oxide with an isoelectric point less than 6.5 and acidification is used, the pH of the acidification treatment needs to be 0.2 to 1 higher than the isoelectric point value of the isoelectric point regulator; and / or, when the isoelectric point regulator is an oxide with an isoelectric point greater than 8.5 and alkalization is used instead of acidification, the pH of the alkalization treatment needs to be 0.3 to 3.5 higher than the isoelectric point value of the isoelectric point regulator.
19. The preparation method according to claim 16, characterized in that, The acidification conditions are as follows: the acidifier in the acidifying agent solution is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, acetic acid, ascorbic acid, hydrogen peroxide, and potassium permanganate; and / or, the concentration of the acidifier in the acidifying agent solution is 0.001~5 mol / L; and / or, the acidification temperature is 30~80℃; and / or, the acidification time is 0.5~8h; and / or, The alkalization conditions are as follows: the alkalizing agent in the alkalizing agent solution is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium bicarbonate, and potassium carbonate; and / or, the concentration of the alkalizing agent in the alkalizing agent solution is 0.005~5 mol / L; and / or, the alkalization temperature is 30~80℃; and / or, the alkalization time is 0.5~8h; and / or, The crystallization conditions are as follows: the solvent used for crystallization is at least one of water, methanol, and ethanol, and / or the crystallization temperature is 120~250℃, and / or the crystallization time is 0.5~18h; and / or, The irradiation conditions are: the radiation source is gamma rays, and / or the irradiation dose rate is 0.01~50 kGy / min, and / or the irradiation time is 0.2~12h.
20. The preparation method according to claim 19, characterized in that, The concentration of the acidifying agent in the acidifying agent solution is 0.01~4 mol / L, and / or the acidification temperature is 35~75℃, and / or the acidification time is 1~6 h; and / or, The concentration of the alkalizing agent in the alkalizing agent solution is 0.01~4 mol / L, and / or the alkalization temperature is 35~75℃, and / or the alkalization time is 1~6h; and / or, The crystallization conditions are as follows: the solvent used for crystallization is at least one of water and ethanol, and / or the crystallization temperature is 150~200℃, and / or the crystallization time is 1~6h; and / or, The irradiation conditions are: the radiation source is gamma rays, and / or the irradiation dose rate is 0.1~25 kGy / min, and / or the irradiation time is 0.2~6h.
21. The application of a hydrogenation catalyst according to any one of claims 1 to 7 or a hydrogenation catalyst obtained by the preparation method according to any one of claims 8 to 20 in the full hydrogenation reaction of C3 and C4 mixed fractions.
Citation Information
Patent Citations
Preparation method of Pd-Cu-series supported hydrogenation catalyst
CN105727990A
C4 fraction selective hydrogenation catalyst and preparation method thereof
CN114100615A
Modified aluminum oxide with high hydroxyl density surface as well as preparation method and application of modified aluminum oxide
CN119551697A
Hydrogenation catalyst, preparation method and uses thereof
CN101433853A
C3 and C4 full hydrogenation catalyst as well as preparation method and application thereof
CN119657125A